2007
DOI: 10.1038/sj.bjc.6603914
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor trichostatin A downregulates human MDR1 (ABCB1) gene expression by a transcription-dependent mechanism in a drug-resistant small cell lung carcinoma cell line model

Abstract: Tumour drug-resistant ABCB1 gene expression is regulated at the chromatin level through epigenetic mechanisms. We examined the effects of the histone deacetylase inhibitor trichostatin A (TSA) on ABCB1 gene expression in small cell lung carcinoma (SCLC) drugsensitive (H69WT) or etoposide-resistant (H69VP) cells. We found that TSA induced an increase in ABCB1 expression in drugsensitive cells, but strongly decreased it in drug-resistant cells. These up-and downregulations occurred at the transcriptional level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
2
38
1
5
Order By: Relevance
“…Considerable experimental evidence suggests that histone acetylation and DNA methylation are involved in this control (16)(17)(18)(19). Consistent with these and other previous studies we also observed that treatments which modulate nuclear architecture could result in ABCB1 up-or down-regulations in various tumour cell lines (3,10,11).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Considerable experimental evidence suggests that histone acetylation and DNA methylation are involved in this control (16)(17)(18)(19). Consistent with these and other previous studies we also observed that treatments which modulate nuclear architecture could result in ABCB1 up-or down-regulations in various tumour cell lines (3,10,11).…”
Section: Discussionsupporting
confidence: 80%
“…It appears that, at the levels of the -50 and -100 GC boxes, ABCB1 promoter display an unmethylated profile in 8226 drug-sensitive cells. This promoter hypomethylation in 8226 cells suggest that ABCB1 repression in drug-sensitive cells could be independent of its promoter methylation, a phenomenon previously reported in H69 and SW620 cells (10,17). On the contrary, 8226-Dox40 drug-resistant cell promoter GC boxes were fully methylated.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations